Impact of Severe Temperature Distortion on Turbine Efficiency - Beard, P; Smith, A; Povey, T (2013)
This paper presents an experimental and computational study of the effect of severe inlet temperature distortion (hot streaks) on the efficiency of the MT1 HP turbine, which is a highly-loaded unshrouded transonic design. The experiments were performed in the Oxford Turbine Research Facility (OTRF) (formerly the TTF at QinetiQ Farnborough): an engine scale, short duration, rotating transonic facility, in which M, Re, Tgas/Twall and N/T01 are matched to engine conditions. The research formed part of the EU Turbine Aero-Thermal External Flows (TATEF II) program. An advanced second generation temperature distortion simulator was developed for this investigation, which allows both radial and circumferential temperature profiles to be simulated. A pronounced profile was used for this study. The system was novel in that it was designed to be compatible with an efficiency measurement system which was also developed for this study. To achieve low uncertainty (bias and precision errors of approximately 1.5% and 0.2% respectively, to 95% confidence), the mass flow rate of the hot and cold streams used to simulate temperature distortion were independently metered upstream of the turbine nozzle using traceable measurement techniques. Turbine power was measured directly with an accurate torque transducer. The efficiency of the test turbine was evaluated experimentally for a uniform inlet temperature condition, and with pronounced temperature distortion. Mechanisms for observed changes in the turbine exit flow field and efficiency are discussed. The data are compared in terms of flow structure to full stage computational fluid dynamics (CFD) performed using the Rolls Royce Hydra code. © 2013 American Society of Mechanical Engineers.